Seroprevalence Neospora caninum in bovines of Lima and comparison between ELISA and IFAT - Serrano-Martínez, Enrique (2018)
The objective of this study was to evaluate the prevalence of antibodies against Neospora caninum in dairy cattle farms of the department of Lima, Peru, and the conconrdance between two diagnostic techniques used for the detection of antibodies in serum: enzyme-linked immunosorbent assay (ELISA) and immunofluorescence antibody test (IFAT). The study was conducted between June 2015 and December 2016 in serum samples of 3407 dairy cattle from 101 farms in Lima (Barranca, Huaura, Huaral, Canta, Lima, Huarochirí, Cañete and Yauyos). The prevalence of infection to N. caninum was 31.0% (1023/3407) by ELISA and 29.9% (1018/3407) by IFAT. The concordance between both diagnostic techniques was good (K=0.98) and statistically significant (p<0.001). Likewise, 69 of the 101 farms were positive (68.3%). The results showed that cattle from Lima dairy farms have moderate individual prevalence and high intra-herd prevalence against N. caninum.